Deontological Feeling: The Tranquil, the Familiar and the Body - Nörenberg, Henning (Frontiers in Psychology, 2021)
This paper contributes to filling a lacuna in recent research on common normative backgrounds. On the one hand, discussions of common normative backgrounds tend to underexpose the role the feeling body plays in relation to the agent’s recognition of deontic powers (obligations, compelling reasons or rights). On the other hand, discussions of bodily background orientations and their role in the agent’s sensitivity to practical significance tend to underexpose the recognition of deontic power. In this paper, I argue that bodily background orientations can contribute to an agent’s sensitivity to deontic power. Developing further on Ratcliffe’s conceptualization of existential feelings, I propose that a person’s bodily background orientation implies responsiveness to an ethically significant kind of affordance, i.e. felt demands. In order to flesh out this theoretical claim, I draw on empirical material concerning a specific existential orientation labelled as “quietism”. Reconstructing its central patterns, I explicate the bodily dimension involved in the quietist orientation as well as the way in which it shapes the responsiveness to felt demands in terms of preserving tranquillity and protecting the familiar. Finally, I discuss the broader theoretical implications of my claim and suggest to categorize ethically relevant bodily background orientations such as the one implicated in the quietist orientation as deontological feelings.